The Conflict of Legal Norms: Islamic Law and Positive Law in the Regulation of Alcoholic Beverages in Pekalongan City - Pratama, Agung Barok; Arum, Dewi Sekar (UIN Sunan Kalijaga Yogyakarta, 2024)
There are inconsistencies between the regulation of alcoholic beverages in Presidential Regulation No. 73/2013 on the Control and Supervision of Alcoholic Beverages and Pekalongan City Regional Regulation No. 13/2000 on the Supervision and Prohibition of Alcoholic Beverages. This article discusses the dialectics of Islamic law and positive law in regulating alcoholic beverages in Pekalongan as a city of santri and its legal consequences. This article is a doctrinal research using statutory, conceptual, and historical approaches. The analysis of legal material is prescriptive to offer arguments to answer problem issues, while the inference technique uses deductive thinking logic. Based on the analysis of Hans Kalsen's norm theory and the principles of legal norm formation, the research shows that the dialectic of Islamic and positive legal norms that produce local regulations on the prohibition of alcoholic beverages in the city of santri is a consequence of the autonomy authority of local governments in making local regulations in order to carry out assistance tasks. Consequently, the local regulation on the prohibition of alcoholic beverages has no binding force because the basic rules of its formation have been declared contrary to law by the Supreme Court, and the content material is contrary to Presidential Regulation No. 74 of 2013. It does not comply with the principles of the formation of local regulations. The legal consequences are uncertainty, regional regulations not following national legal policy, and the potential to cause discrimination. This article presents an understanding of the dialectic of Islamic law on the one hand and positive law on the other regarding regulating the circulation of alcoholic beverages. Terdapat inkonsistensi pada regulasi minuman beralkohol dalam Peraturan Presiden Nomor 73 Tahun 2013 Tentang Pengendalian dan Pengawasan Minuman Beralkohol dengan Peraturan Daerah Kota Pekalongan Nomor 13 Tahun 2000 Tentang Pengawasan dan Pelarangan Minuman Beralkohol. Artikel ini membahas dialektika hukum islam dan hukum positif dalam pengaturan minuman beralkohol di kota Pekalongan sebagai kota santri serta akibat hukumnya. Artikel ini merupakan penelitian doktrinal menggunakan pendekatan undang-undang, konseptual dan historis. Analisis materi hukum bersifat preskriptif dengan maksud untuk menawarkan argumen untuk menjawab masalah masalah, sedangkan teknik inferensi menggunakan logika berpikir deduktif. Berdasarkan analisis teori norma Hans Kalsen dan asas-asas pembentukan norma hukum, penelitian menunjukkan bahwa dialektika norma hukum Islam dan positif yang menghasilkan peraturan daerah tentang larangan minuman beralkohol di kota santri merupakan konsekuensi dari kewenangan otonomi pemerintah daerah dalam membuat peraturan daerah dalam rangka melaksanakan tugas pendampingan. Akibatnya, keberadaan peraturan daerah tentang larangan minuman beralkohol a quo sebenarnya tidak memiliki kekuatan yang mengikat karena aturan dasar pembentukannya telah dinyatakan bertentangan dengan hukum oleh Mahkamah Agung dan materi isinya bertentangan dengan Peraturan Presiden No. 74 Tahun 2013 dan tidak sesuai dengan prinsip-prinsip pembentukan peraturan daerah. Konsekuensi hukumnya adalah ketidakpastian hukum, keberadaan peraturan daerah tidak sesuai dengan kebijakan hukum nasional dan berpotensi menimbulkan diskriminasi. Artikel ini menyajikan pemahaman mengenai dialektika hukum islam di satu sisi, dan hukum positif di sisi lain mengenai bagaimana praktik pengaturan peredaran minuman beralkohol.